2016
DOI: 10.5137/1019-5149.jtn.18736-16.1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of time-to-surgery on outcome in patients with neurological deficits caused by spinal tuberculosis

Abstract: The duration of neurological symptoms, but not the grade of neurological involvement, is correlated with postoperative neurological recovery of patients with neurological deficits caused by spinal TB. However, reducing preoperative chemotherapy does not significantly yield improved outcomes; therefore, undergoing four weeks of preoperative chemotherapy is acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The majority of patients with ASIA B recovered to ASIA C or D postoperatively. 12,14 Other patients with ASIA C recovered to ASIA D or E in a 9-12-month period. One study was done by Choi et al, which showed neurological recovery in 63-65% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of patients with ASIA B recovered to ASIA C or D postoperatively. 12,14 Other patients with ASIA C recovered to ASIA D or E in a 9-12-month period. One study was done by Choi et al, which showed neurological recovery in 63-65% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…These are isoniazid, rifampicin, pyrazinamide, ethambutol. 14 These are given according to body weight. Patients who fail medical management or those who develop neurological deficits, spinal deformities, or severe pain due to spinal instability need surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy and surgery are the main treatment for spinal TB (2). The aim of the surgery is to relieve the compression of the spinal cord or nerve, reconstruct spinal stability, and correct kyphosis deformity (3,4). Radical debridement of the TB lesion is the key to spinal TB surgery (5), but the vertebral defect is often left after the debridement, thus a bone graft is of great importance to restore the height of the vertebral body and rebuild the spinal stability (6).…”
Section: Introductionmentioning
confidence: 99%